(untitled) (Research, Society and Development, 2021)
Control is of paramount importance for the industry, both for employee safety and for the economic side, through which it is possible to increase the quality of the final product and reduce costs. There are several ways to perform the control, one of them is through optimization methods and bioinspired algorithms such as the firefly colony algorithm, such methods minimize the error between the output signal of the controlled variable and the setpoint (desired value). This work aimed to perform and evaluate the efficiency of modeling and digital control of the liquid level of a pilot plant using the firefly colony algorithm. The results were obtained through simulations carried out in Scilab software and experiments in a pilot plant. The results indicated that for this type of system the firefly colony algorithm obtained high efficiency PI controllers, reconciling robustness, performance and no overshoot (maximum deviation of the controlled variable with the setpoint value).